2020
DOI: 10.1186/s40981-020-00383-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing cerebrospinal fluid from mepivacaine using the pH test in patients undergoing elective cesarean section with combined spinal-epidural anesthesia

Abstract: Introduction In single-space combined spinal-epidural anesthesia (CSEA), it is important to correctly determine if the fluid coming out of the spinal needle is cerebrospinal fluid (CSF) or the liquid used in the loss of resistance (LOR) technique. In this study, we used mepivacaine for LOR and measured the pH values of CSF and mepivacaine to determine whether the pH test is a reliable method to confirm CSF when performing single-space CSEA. Methods This clinical trial included 47 full-term pregnant women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…1 Those older studies cautioned, however, that no single test is perfect, and suggested the use of a combination of tests. In more recent literature, the use of glucose and pH has been revisited, 3,4 to varying degrees of success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Those older studies cautioned, however, that no single test is perfect, and suggested the use of a combination of tests. In more recent literature, the use of glucose and pH has been revisited, 3,4 to varying degrees of success.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, clear fluid at the needle hub may represent either a) iatrogenic fluid, b) cerebrospinal fluid (CSF) that leaked after a previous procedure or c) intrathecal CSF from a new dural puncture. Evolving literature exists on differentiating local anesthetic, [1][2][3] and normal saline 4 from CSF; however, none of the tests discussed are currently standard of care in a major guideline. To our knowledge, there is no mention of fluid from prior CSF collection versus CSF from new dural puncture.…”
Section: Introductionmentioning
confidence: 99%